Governance, Public Expenditure, Trade and Poverty Reduction in Sub-Saharan African Countries - Ali Madina Dankumo; Suryati Ishak; Yasmin Bani; Hanny Zurinah Hamza (Jurnal Ekonomi dan Studi Pembangunan, 2021)
When policies and programmes are designed and implemented successfully by governments, it tends to improve development indices such as reducing poverty, when governance is good. The paper examined the impact of governance, public expenditure and trade on poverty reduction in some selected Sub-Saharan African countries, using Pool Mean Group (PMG) with data spanned for 21 years (1996-2016). The results show a long-run association between governance, public expenditure, trade and poverty reduction in SSA. Also, control of corruption, political stability, government expenditure, and trade reduces poverty by enhancing the Human Development Index (HDI) in the long run. This outcome implies that improving governance (control of corruption and political stability) is vital for reducing poverty as it increases the adequate performance of public expenditure and as well as promote trade in SSA.